Natural immunogenic properties of bioinformatically predicted linear B-cell epitopes of dengue envelope and pre-membrane proteins - Mahesha N. Nadugala (BMC, 2021)
Abstract Background The natural antibody responses to B-cell epitopes from dengue structural proteins were assessed using immune sera from people having well-defined past dengue infections with one of the four serotypes. Method Based on an immune-computational analysis previously conducted, nineteen epitopes from the envelope (E) and eight epitopes from pre-membrane (prM), which were more than 50% conserved across all the four DENV serotypes, were selected. Peptides to represent these B-cell epitopes were obtained from commercially available arrays, and were subjected to enzyme linked immunosorbent assay with sera obtained from dengue seropositive healthy volunteers (DENV1 n = 12: DENV2 n = 12: DENV3 n = 12 and DENV4 n = 12), and 10 dengue seronegative healthy volunteers from Sri Lanka. The cut-off value for the positive antibody response was set by taking the mean response of a peptide to the negative sera plus three standard deviations. The peptides (N = 7) showing the broad immune responses were used to generate antibodies in three mice (Balb/c) batches. The mice antisera were then subjected to microneutralization assays against all the four DENV serotypes. An EC50 viral neutralization ≥ 40 times the serum dilution was considered as neutralizing. Results Five of the E-peptide and two prM peptides were recognised by most individuls exposed to infections with each of the four serotypes, showing a serotype cross-reactive broad antibody response. The mice immune sera against the peptides representing the five E protein epitopes neutralized all the four DENV serotypes. Two of these five epitopes are from the Domain II, whereas one of them includes the whole bc-loop region. Conclusion The antibody responses of highly conserved epitopes across the serotypes, were broadly responsive with sera of all four DENV serotypes collected from individuals infected with only one DENV serotype. Weakly conserved epitopes showed rather specific antibody responses dominated by one or few serotypes.